PERBANDINGAN MOTHER WAVELET DALAM SISTEM TEMU KEMBALI INFORMASI KEMIRIPAN MOTIF KAIN TENUN SULAWESI TENGGARA - Wa Ode Rizqanun Karyima Bolu; Muh. Ihsan Sarita; Ika Purwanti Ningrum (Informatics Engineering Department of Halu Oleo University, 2019)
Information retrieval is a process, method, and procedure used to select relevant information and stored in a database. In libraries and archives, information retrieval is usually for known documents or for information about certain subjects. Information Retrieval System is used to rediscover information that is relevant to the needs of users of a collection of information automatically. Weaving motifs can be distinguished by the naked eye but not all people can distinguish motifs from each type of woven fabric due to the difficulty in defining the characteristics of woven fabric motifs from an area and the variety of motifs and compositions of colors available. Based on the data and facts that have been mentioned, wavelet can be used for extracting texture features in the Information Retrieval System, but further research is nApplication of Mother Wavelet in Retrieval System Similarity Information on Southeast Sulawesi Woven Fabric Motives gives good results needed to compare the optimal mother wavelet for the system. and among 4 types of wavelets, Haar with decomposition level 7 is the best feature extraction method compared to Daubechies 4, Symlets 2 and Coiflets 1. This is evidenced by faster computing time and the best percentage of precision, which is 95%.Keywords— Mother Wavelet, Information Retrieval, Weaving. DOI : 10.5281/zenodo.2649780